Locating DNA within fingermarks using fluorescent in situ detection; a collaboration between ESR and Flinders University. (29th July 2019) - Haines, Alicia M.; Kanokwongnuwut, Piyamas; Harbison, SallyAnn; Cockerton, Sarah; Linacre, Adrian
ABSTRACT: A pilot study on the detection of DNA in fingermarks using fluorescent in situ detection after different time periods since hand washing was undertaken by Flinders University. Collaboration was sought to show the ability to obtain similar results within different laboratories. The Institute of Environmental Science and Research (ESR) was involved in this inter-laboratory study in collaboration with Flinders University. The newly developed method involves the use of Diamond Nucleic Acid dye for the staining of fingermarks (20× concentration in 75% ethanol) using a hand-held microscope (Dino-Lite Edge Digital Microscope). Fingermarks were deposited by volunteers onto glass slides at varying time intervals after hand washing (2, 5, 15, 30, 60 and 180 minutes). The amount of cellular debris was calculated by counting the fluorescent dots present in three fields of view and estimating the amount of transferred cellular material for each fingermark. This article will outline the results obtained from ESR and how they compare with results already collated from Flinders University.